PENGENDALIAN MUTU PRODUK BAKSO-SOSIS (BASIS) DENGAN METODE P-CHART, DIAGRAM PARETO DAN DIAGRAM ISHIKAWA (Studi Kasus di PT. Sumber Prima Anugrah Abadi Tangerang, Banten) - , VITA SOTAGAMA; , Dr. Wagiman, STP, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
PT. Sumber Prima Anugrah Abadi is a meat processing industry that processing such as meatball, sausage, basis (meatball-sausage), and smoked beef. Quality control has an important role to success production activity. The company has been charged to create a product that has a quality to fulfill consumer necessary. Therefore, control has been needed to create a product. One of the technique that can be used to quality control were seven tools. The seven tools were used to quality control are p-chart, pareto diagram, and ishikawa diagram. P-chart analysis result indicate that the production process were out of control or diverge. The control graphic were showed that there are 2 points out of control specifically in august 12th and 15th production. Based on pareto diagram, repair priority that have to be done for dominant failure consecutively such as short flaw (33%), long flaw (30%), hollow flaw (22%), and cut flaw (15%). Based on ishikawa diagram analysis, failure factor come from method specifically machine checking that were not done periodically and SOP were not done properly.